Pulsed electric fields (PEF) as hot air drying pre-treatment: Effect on quality and functional properties of saffron (Crocus sativus L.). (January 2021) - Neri, Lilia; Giancaterino, Marianna; Rocchi, Rachele; Tylewicz, Urszula; Valbonetti, Luca; Faieta, Marco; Pittia, Paola
Abstract: This study aimed to investigate the use of pulsed electric fields (PEF) (2 kV/ cm; 1.5 KJ kg −1 ) as pre-treatment to the hot air drying process for the improvement of quality and functional properties of saffron. Analysis of flavouring, aroma and colouring strength (E 1% λmax ), crocins pattern (UHPLC-MS/MS), total polyphenol content (TPC) and antioxidant activity (AOA) were performed after processing and during aging at room temperature. Microstructure of fresh and processed stigmas was also assessed. PEF decreased (≈ −41%) the flavour, aroma and colouring strength of stigmas and negatively influenced the safranal production during drying; nevertheless, stigmas pre-treated by PEF (PD) after 3 months of aging showed quality properties similar to those of not pre-treated sample (D). Analysis of crocins by UHPLC-MS/MS highlighted a negative effect of PEF on trans-cis crocins ratio and showed poor correlation with colour strength. PEF did not influence the TPC of fresh stigmas but after drying and aging PD showed the highest value among the samples. PEF negatively influenced (−24%) the AOA of fresh stigma while favored its increase during drying. Loss of AOA during aging (up to 86%) was processing independent. Microstructure analysis showed that PEF treatment strongly impaired the stigmas' cells, thus enhancing the extractability of intracellular compounds. Highlights: PEF was applied as drying pre-treatment to increase saffron quality and functionality. PEF affected the flavour, aroma and colouring strength of saffron stigmas. PEF decreased the trans/cis crocins ratio in fresh stigmas. Safranal production during drying and aging was influenced by PEF. PEF affected the biogenesis and extractability of colouring and flavouring compounds.